Renal and Bladder Cancer During Pregnancy: A Review of 47 Cases and Literature-based Recommendations for Management - Maggen, Charlotte; Linssen, Jasmijn; Gziri, Mina Mhallem; Zola, Paolo; Cardonick, Elyce; de Groot, Christianne J M; Garcia, Alvaro Cabrera; Fruscio, Robert; Drochytek, Vit; Van Calsteren, Kristel; Albersen, Maarten; Amant, Frédéric; et al. (Urology, 2021)
OBJECTIVE: To provide contemporary gestational age-specific recommendations for management, a retrospective series of patients with renal or bladder cancer during pregnancy is reported. METHODS: Obstetric and oncological data of pregnant patients with a diagnosis of renal or bladder cancer were selected from the worldwide registry of the International Network of Cancer, Infertility and Pregnancy. In addition, the literature was reviewed for recent case reports since last reviews in 2014 for renal cancer and 2004 for bladder cancer. RESULTS: International Network of Cancer, Infertility and Pregnancy registered 22 cases (14 renal cancer and 8 bladder cancer), diagnosed between 1999 and 2017, and the literature reported 15 cases with renal cancer and 10 cases with bladder cancer between 2004 and 2019. Most common symptoms for renal and bladder cancer were pain (28%) and hematuria (66%), respectively. In more than half of the patients, surgical treatment was performed during pregnancy. Preterm deliveries were mostly medically induced (12 of 17, 71%) and all patients with a planned delivery before 34 weeks had advanced cancer. For renal and bladder cancer respectively, 79% and 87% of patients obtained complete remission. Advanced cancer stages had worse prognosis; 3 of 7 patients with known follow-up deceased within 15 months after diagnosis. CONCLUSION: Gestational age at diagnosis determines further management of renal and bladder cancers during pregnancy. Advanced stages challenge decision-making. The maternal needs for immediate treatment, and the neonatal risks including the impact of a preterm delivery should be discussed in a multidisciplinary setting while respecting the patient's autonomy.
Keywords: Young Adult; nádory ledvin; Labor, Induced; Pregnancy Complications, Neoplastic; retrospektivní studie; mladý dospělý; nádory močového měchýře; předčasný porod; Pregnancy; těhotenství; Adult; Kidney Neoplasms; Pain; dospělí; Premature Birth; registrace; indukovaný porod; novorozenec; bolest; lidé; ženské pohlaví; Humans; Infant, Newborn; Hematuria; Registries; Retrospective Studies; Urinary Bladder Neoplasms; Female; hematurie; lidé středního věku; nádorové komplikace v těhotenství; Middle Aged